2007
DOI: 10.2215/cjn.02510706
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Concentrations of IL-6 and Elevated APACHE II Score Predict Acute Kidney Injury in Patients with Severe Sepsis

Abstract: Acute kidney injury (AKI) is common in critically ill patients with severe sepsis (SS), and the predictors of AKI in this population have not been well characterized. The study group was the placebo group of the Prospective Recombinant Human Activated Protein C Worldwide Evaluation in Severe Sepsis (PROWESS) data set. PROWESS is a prospective, randomized, controlled study of the use of drotrecogin ␣ (activated) for the treatment of SS. Placebo patients who had an admission renal sepsis organ failure score of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
108
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 42 publications
15
108
1
3
Order By: Relevance
“…Previously, two studies showed that APACHE II score aids to predict AKI in patients with sepsis. 30,35 As expected, APACHE II was a predictor of sepsis-related-AKI in our study. Because APACHE II score contains 12 routine physiological components, no single parameter of APACHE II could predict sepsis-related-AKI according to our results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previously, two studies showed that APACHE II score aids to predict AKI in patients with sepsis. 30,35 As expected, APACHE II was a predictor of sepsis-related-AKI in our study. Because APACHE II score contains 12 routine physiological components, no single parameter of APACHE II could predict sepsis-related-AKI according to our results.…”
Section: Discussionsupporting
confidence: 85%
“…28,29 Clinical studies revealed that IL-6, procalcitonin (PCT) can be used as a predictive marker for sepsis-related-AKI in patients with sepsis. 30,31 In accordance with these studies, we showed that baseline NLR is fruitful and strong predictor of sepsis-related-AKI. Urine NGAL, L-type fatty acid-binding protein (L-FABP) is new and useful markers for early detection of AKI in critically ill adults with an eGFR over 60 mL/min per 1.73 m 2 .…”
Section: Discussionsupporting
confidence: 84%
“…In the Norasept II study (29), there was a trend toward higher IL-6 levels in those subjects who subsequently developed acute kidney injury, but this result did not quite achieve statistical significance. More recently, in a secondary analysis of the PROWESS clinical trial of activated protein C for the treatment of severe sepsis, Chawla et al (32) demonstrated that baseline IL-6 levels were predictive for acute kidney injury. Our results are consistent with these findings and suggest that IL-6 is predictive in other critically ill patient populations, namely, those with acute lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Because patients who develop AKI and CKD also tend to have risk factors for cardiovascular disease (e.g., diabetes mellitus, hypertension, and hypercholesterolemia), some authors have suggested that the increased cardiovascular events and excess mortality outcomes seen in patients with kidney disease (both AKI and CKD) are largely an epiphenomenon due to shared risk factors (7,(17)(18)(19)(20)(21). AKI is associated with the development of CKD, and CKD is also a robust risk factor for major adverse cardiovascular events (MACE) (22).…”
Section: Introductionmentioning
confidence: 99%